Colégio Normal Francisca Mendes: caminhos da escola normal em Catolé do Rocha/PB 1939 a 1959 - Sousa, Maria Cleide Soares de (2012)
This research is the result of a fulfilled investigation concerning the Colégio Normal Francisca Mendes, in the town of Catolé do Rocha, from 1939 to 1959. The Colégio was the object and the locus of this study, with emphasis on its creation, functioning and outcome of its school culture as formation institution of future teachers. The main objective was to analyze the creation and functioning process of the Colégio, especially in relation to information about the historical context of that educational period referring to the XX century and themes regarding school culture. As to the methodology used, it is an approach of basic research, documental character and qualitative nature. For data collection, the Oral History technique was used, by means of field research and semi-structured interviews carried out with six students and a teacher of the Colégio. In order to analyze the collected data, the content analysis method was used by perceiving that the specificity of the object of this study prompts the dialogue with students through their memories, materials related to school organization and pedagogical practices developed in the formation institution. Results point out, with certainty, that the creation of a school institution, in a scenario of a town placed in Paraíba hinterlands, in the end of the 1930s, presents a relevant meaning. Such importance is represented, especially, for being a formation institution for Elementary teachers, Escola Normal, of a school which contributes to the access to education and to the development of the local and regional society. Therefore, it constitutes an object of historiographic interest once the Colégio Normal Francisca Mendes contributes so as its social function, both in the town and in Paraíba State, can be understood.